Magnetic and spectrometric studies of Al-Gor area, Southwestern Sinai, Egypt - ZAEIMAH, Mostafa A. M. (Contributions to Geophysics and Geodesy, 2021)
Al-Gor area is a part of Southwestern Sinai of Egypt. It is considered as one of the most promising areas for mineralization in Egypt, being rich in many mineral deposits of: manganese, iron, copper, zinc, lead, cobalt, nickel, silver, gibbsite, and uranium. Besides, some industrial ore minerals such as kaolin and glass sand,… etc. are also found in this area. The area was studied by Gama-ray spectrometry to trace the radioactive anomalies, their concentrations and their relationship to the existing rocks, and by magnetic survey to study the relationship of radioactive anomalies and their trends with the trends of geological structures. The gamma-ray spectrometric maps show different levels over the surveyed area, which reflect contrasting radioelement contents for the exposed various rock types. The highest radiospectrometric levels are located in the northwest southeast direction and some scattered parts all over the study area. They are mainly associated with Um-Bogma Formation, bearing gibbsite. The study area possesses radiospectrometric ranging between 0.6 and 110.9 Ur as a total-count, 0.1 to 1.8 % for K, 0.1 to 99 ppm for eU and 0.1 to 23 ppm for eTh. The qualitative analyses of magnetic data show the existences of a number of different magnetic anomalies, with different amplitudes and frequencies as well as trends. From the application of spectral analyses of magnetic data, the regional and residual depths of magnetic anomalies can be computed. The first depth represents the regional (deep-seated) anomalies, at about 75 m and the residual (shallow-seated) anomalies, at about 20 m. The trends of the structures as derived from the spectrometric and ratio maps correspond to those inferred from the residual-component magnetic map, which reflects the effect of structures on the concentration of radioactive elements and, consequently mineralization.